Dilemmas Of Strategic Planning in Contemporary Universities Environments - Jamal Asad Mezel (QALAAI ZANIST JOURNAL, 2024)
Planning has gained importance among practitioners and academics. In light of the current requirement for creative activities, this study examines the difficulties facing planning agencies, particularly at universities, with regard to environmental planning. The article provides a comprehensive overview of three particular problems of the current requirement for creative activities, this study examines the difficulties facing planning agencies, particularly at universities, with regard to environmental planning. The article provides a comprehensive overview of three particular problems. The conflicts between intervention, regulation, and investment are distinguished and theoretically explored. This paper offers knowledge of the planning dilemmas that exist today at academic institutions by examining the crucial concepts of time and space in the intervention dilemma, material and procedural standards in the regulation dilemma, and risk and income in the investment dilemma. This study suggests that in order to develop new contextualized forms of synthesis, planning practice at academic institutions today has to make sense of these dilemmas. Because of the intense competition among higher education institutions, strategic planning is crucial to their survival and success.